O processo de apropriação do desenho à escrita - Campos, Camila Torricelli de (2011)
The focus of this research is to understand how is the process of writing appropriation, while symbolic representation in children ranging between 5 to 7 years old. The study is longitudinal nature, characterized by analysis accounts developed in a long period of time. It was analyzed written productions of two children, already stored in a database during the period of 3 years. The theoretical framework was guided by the historical-cultural perspective, focusing authors like Vygotsky and Luria. Methodological assumptions were used as the evidential paradigm, to allow qualitative analysis. This paradigm was developed within the humanities and used to make assumptions about the development of graphic language of children, since the moment they begin to draw until to write. From the clues left in the productions collected, in search of understand the process of writing appropriation for these children. For this to be asked: What mark writing children 4 to 7 years leave in their graphic activities that indicate the process appropriation of writing? In order to answer this question was raised as a general objective describe and analyze the appropriation process of writing as the object of analysis marks leave on the graphic activities for children from 4 years until they the symbolic writing. It is worth noting there are few studies in the area of literacy with this character, and thus an important contribution into the topic, especially for studies of the historical-cultural theory. . It was possible to see in research throughout the course of written language acquisition, that the relationship between drawing and writing was linked to the need for children to express themselves when exposed to situations they might experience and show "some way" - drawing or writing - the useful and function of language. Autonomy in children's writing was when what they wanted to "say" couldn‟t be expressed only by his drawings. As they were appropriating this new language, writing, this became the main form of representation in their productions. The research may also contribute to the training area of literacy teachers, since their product can provide new ways for action towards the students.